Satisficing behavior with a secondary criterion - Christopher J. Tyson (Queen Mary University of London, School of Economics and Finance, 2014)
Using the techniques of revealed preference analysis, we study a two-stage model of choice behavior. In the first stage, the decision maker maximizes a menu-dependent binary relation encoding preferences that are imperfectly perceived. In the second, a menu-independent binary relation is maximized over the subset of alternatives that survive the first stage. This structure can support various interpretations, including those of salience effects, positive action, and surface characteristics. We characterize the model behaviorally both in ordinal form and in terms of the corresponding numerical representations.
Keywords: D01; D03; 330; Bounded rationality; Choice function; Revealed preference; Salience